2020
DOI: 10.3390/fractalfract4020019
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Kinetic Equations Associated with Incomplete I-Functions

Abstract: In this paper, we investigate the solution of fractional kinetic equation (FKE) associated with the incomplete I-function (IIF) by using the well-known integral transform (Laplace transform). The FKE plays a great role in solving astrophysical problems. The solutions are represented in terms of IIF. Next, we present some interesting corollaries by specializing the parameters of IIF in the form of simpler special functions and also mention a few known results, which are very useful in solving physical or real-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To investigate the RY186 dye degradation kinetics, experimental datas were analyzed. The data were found to be accommodated by the pseudo‐first‐order model 27–30 . The kinetics was studied to find the reaction rate constant K 1 for 0.0227 g/l/min for decolorization processes and its efficiency in the PEF process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the RY186 dye degradation kinetics, experimental datas were analyzed. The data were found to be accommodated by the pseudo‐first‐order model 27–30 . The kinetics was studied to find the reaction rate constant K 1 for 0.0227 g/l/min for decolorization processes and its efficiency in the PEF process.…”
Section: Resultsmentioning
confidence: 99%
“…The data were found to be accommodated by the pseudo-first-order model. [27][28][29][30] The kinetics was studied to find the reaction rate constant K 1 for 0.0227 g/l/min for decolorization processes and its efficiency in the PEF process. The experimental study was carried out at optimized conditions of a dye concentration, pH, Fe 2+ , H 2 O 2 , and current density constant at 0.15 g/l 3.0, 0.015 g/ l, 0.2 g/l, and 0.1 mA/cm 2 were plotted, and it was found that the process obeys pseudo-first-order kinetic and the studies found to fit the data well (R 2 = 0.9824) shown in Figure 8.…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…Manzoor et al [2] developed a Beta operator in terms that was based on the extended Mittag-Leffler function with Caputo fractional differentiation. Bansal et al [3] used the well-known integral transform to solve the fractional kinetic equation (FKE) associated with the incomplete I-function (IIF) (Laplace transform). The dualities between the Laplace-Carson transform and other useful integral transforms have been described by Chauhan et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…In [1], the solution of a fractional kinetic equation (FKE), associated with the incomplete I-function (IIF) by using the well-known integral transform (Laplace transform), was investigated. The FKE plays an important role in solving astrophysical problems.…”
mentioning
confidence: 99%